The Most Appropriate Lexical Unit for L2 Vocabulary Research and Pedagogy: A Brief Review of the Evidence. (27th November 2020) - Brown, Dale; Stoeckel, Tim; Mclean, Stuart; Stewart, Jeff
Abstract: The choice of lexical unit is a significant issue in L2 vocabulary research and pedagogy. This brief review examines two important questions bearing on this issue: (i) How encompassing a lexical unit can learners deal with receptively? and (ii) How much difference does the choice of lexical unit make in practice? Regarding the former, empirical evidence from studies with L2-English learners shows that the broad 'word family' unit, requiring considerable knowledge of affixes and the ability to apply this knowledge, cannot be supported. Regarding the latter, estimates of the proportion of English text consisting of derivational forms vary due to differences in approach and text type examined. However, even the smallest estimate is of a magnitude sufficient to have a meaningful impact on text comprehension. Accordingly, this review suggests that the most appropriate lexical unit may be the lemma or flemma. This conclusion has major implications for L2 vocabulary research, with regards to vocabulary testing and estimates of learning needs, and for L2 vocabulary pedagogy, in respect of curriculum planning and the use of word lists.